Three mechanisms control E-cadherin localization to the zonula adherens - Woichansky, Innokenty; Beretta, Carlo Antonio; Berns, Nicola; Riechmann, Veit (Nature Communications, 2016)
E-cadherin localization to the zonula adherens is fundamental for epithelial differentiation but the mechanisms controlling localization are unclear. Using the Drosophila follicular epithelium we genetically dissect E-cadherin transport in an in vivo model. We distinguish three mechanisms mediating E-cadherin accumulation at the zonula adherens. Two membrane trafficking pathways deliver newly synthesized E-cadherin to the plasma membrane. One is Rab11 dependent and targets E-cadherin directly to the zonula adherens, while the other transports E-cadherin to the lateral membrane. Lateral E-cadherin reaches the zonula adherens by endocytosis and targeted recycling. We show that this pathway is dependent on RabX1, which provides a functional link between early and recycling endosomes. Moreover, we show that lateral E-cadherin is transported to the zonula adherens by an apically directed flow within the plasma membrane. Differential activation of these pathways could facilitate cell shape changes during morphogenesis, while their misregulation compromises cell adhesion and tissue architecture in differentiated epithelia.